1968
DOI: 10.2466/pms.1968.26.1.311
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Control of Differentiation in the Perception of Persons and Objects

Abstract: Performances in tests of 4 dimensions of cognitive control that have implications for the differentiation of experience were used as bases for prediction of response to additional cognitive tests, including a Semantic Differential procedure designed to sample one aspect of differentiation in the perception of persons and objects. Factor analysis was used as a means of assessing relationships among the variables and their relationship to the sex of S. Use of husband-wife pairs as Ss provided partial control of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
1

Year Published

1971
1971
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 20 publications
0
4
0
1
Order By: Relevance
“…Apart from the question of sex differences, several studies also have shown differences between field-dependent and field-independent subjects on a variety of tasks involving social and/or self-cognition, and these results have been regarded as support for the concept of psychological differentiation as a broad dimension of cognition. In research using a variety of measures and procedures, field-independent subjects have been found to use more finely discriminated constructs in the perception of other people (Gardner et al, 1968;Rhodes et al, 1968;Kavenaugh &Weissenberg, 1973 andO'Leary et al, 1974). Witkin et al (1962) also report that field-independent subjects hold relatively articulated concepts of their own bodies and a clearer sense of the self as distinct from others.…”
mentioning
confidence: 99%
“…Apart from the question of sex differences, several studies also have shown differences between field-dependent and field-independent subjects on a variety of tasks involving social and/or self-cognition, and these results have been regarded as support for the concept of psychological differentiation as a broad dimension of cognition. In research using a variety of measures and procedures, field-independent subjects have been found to use more finely discriminated constructs in the perception of other people (Gardner et al, 1968;Rhodes et al, 1968;Kavenaugh &Weissenberg, 1973 andO'Leary et al, 1974). Witkin et al (1962) also report that field-independent subjects hold relatively articulated concepts of their own bodies and a clearer sense of the self as distinct from others.…”
mentioning
confidence: 99%
“…In the view of cognitive psychology, cognitive style manifests itself already at the level of creating image representations (memory images), which means that it is connected with the preferred way of viewing data field (local-global level) (Navon, 1977), with the efficiency of information selection of attention mechanisms (Carver, Scheier, 1981;Gardner & Lorenz, 1968;Nosal, 1990) and the capacity of working memory and efficiency of searching and processing the data stored in it (Baddeley, 2000(Baddeley, , 2002Miyake et al, 2001). The local-global level means either concentrating on perceiving the entire structure as multiple elements combined together and on spontaneous identification of the details selected from the background, or on global perception of the central figure, not taking into account the details which form it (Navon, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The first style parameter "Analyticity-syntheticity" was highlighted by Gardner, Lohrenz, and Schoen (1968), and is associated with the concepts of "range of cognitive equivalence" and "sorting of objects" (p. 311). This parameter differentiates people according to what they are more focused on in the process of cognition: on distinction or on similarity, on specific in the observed phenomena or on the general.…”
Section: Research Questionsmentioning
confidence: 99%
“…Cognitive style, reflecting various aspects of the functioning of the cognitive sphere, is a stable individual characteristic of the ways a person interacts with the information field. The closest attention was paid to such behavioral parameters as field-dependence-independence (Witkin & Goodenough, 1982), impulsivity-reflexivity (Kagan, 1986), analyticity-synthetics or conceptual differentiation (Gardner, Lohrenz, & Schoen, 1968) and others.…”
Section: Introductionmentioning
confidence: 99%